STUDI LITERATUR SISTEMATIS TENTANG POLA ASUH ORANG TUA DAN PERKEMBANGAN SOSIAL ANAK USIA DINI - Yuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this systematic literature review is to investigate the relationship between early childhood social development and parenting styles. The Systematic Literature Review (SLR) method was used to analyze recent scholarly publications from 2020 to 2025, as well as books published within the last ten years, using databases such as Google Scholar, DOAJ, SINTA, and GARUDA. The review reveals that democratic parenting supports children's social development by enhancing empathy, cooperation, and emotional communication skills. In contrast, authoritarian and permissive parenting tend to hinder the development of children's social skills due to either a lack of boundaries or excessive control. Furthermore, this study highlights the importance of parental education and collaboration between families and educational institutions to achieve ideal parenting practices. It also recommends the development of culturally relevant and evidence-based mentoring programs in early childhood education settings. These findings provide a foundation for designing parenting interventions and social-emotional learning methods in early childhood education.